2021
DOI: 10.1093/brain/awab359
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis identifies impaired axonogenesis in chronic overlapping pain conditions

Abstract: Chronic pain is often present at more than one anatomical location, leading to chronic overlapping pain conditions (COPC). Whether COPC represents a distinct pathophysiology from the occurrence of pain at only one site is unknown. Using genome-wide approaches, we compared genetic determinants of chronic single-site vs. multisite pain in the UK Biobank. We found that different genetic signals underlie chronic single-site and multisite pain with much stronger genetic contributions for the latter. Among 23 loci a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 77 publications
8
51
0
Order By: Relevance
“…The hypersensitivity effect is submodality-selective as shown by the finding that netrin-1 did not influence heat nociception. The hypersensitivity effect of netrin-1 in the present study is in line with earlier results reporting that netrin-1 is associated with pain in various experimental and pathophysiological conditions [ 5 , 6 , 7 , 8 , 9 , 13 ] and that the DCC receptor, a key mediator of attractive signaling by netrin-1 [ 2 ], may be mediating pronociceptive effects of netrin-1 [ 5 , 6 , 7 , 11 , 13 ]. The present study extends earlier findings by showing that a single intrathecal dose of netrin-1 does not only induce acute hypersensitivity in rodents [ 7 ], but it may induce a prolonged neuropathy-like pain hypersensitivity condition lasting at least up to three weeks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The hypersensitivity effect is submodality-selective as shown by the finding that netrin-1 did not influence heat nociception. The hypersensitivity effect of netrin-1 in the present study is in line with earlier results reporting that netrin-1 is associated with pain in various experimental and pathophysiological conditions [ 5 , 6 , 7 , 8 , 9 , 13 ] and that the DCC receptor, a key mediator of attractive signaling by netrin-1 [ 2 ], may be mediating pronociceptive effects of netrin-1 [ 5 , 6 , 7 , 11 , 13 ]. The present study extends earlier findings by showing that a single intrathecal dose of netrin-1 does not only induce acute hypersensitivity in rodents [ 7 ], but it may induce a prolonged neuropathy-like pain hypersensitivity condition lasting at least up to three weeks.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, human studies have reported that in patients with endometriosis, netrin-1 and DCC levels are increased in endometrial tissues [ 11 ], and patients with small fiber neuropathy have increased netrin-1 gene expression in keratinocytes [ 12 ]. In genome-wide analysis, the DCC netrin-1 receptor gene was identified as the top gene associated with multisite pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic overlap with non-pain conditions was suggestive of the complexity of factors contributing to chronic pain. Furthermore, DCC , the top gene associated with F1, was also the top gene reported in a recent study of chronic overlapping pain conditions (COPCs), which used pain for more than 3 months in different body sites from the UKBB (head, face, neck/shoulder, back, stomach, hip, knee, all over the body) [59]. Of the 241 genes mapped to independent significant SNPs from the F1 GWAS, FKBP5 was the only one previously targeted in a candidate gene study (as opposed to GWAS) for posttraumatic musculoskeletal pain [144, 10].…”
Section: Resultsmentioning
confidence: 99%
“…The UKBB is a large and extensively phenotyped cohort, which recently added First Occurrences data (category 1712), giving researchers access to primary care and death register records to supplement self-reports and ICD-10 diagnoses, earlier available exclusively from hospital intake records. This growing trove of genotypic and phenotypic data has enabled us to examine a much larger number of pain conditions than reported in prior genetic studies of multi-site pain [58, 56, 59, 120]. Our work builds on earlier studies, which included smaller numbers of conditions, often selected a priori based on anatomic proximity or hypothesized etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation